GOOGLE MEET SEBAGAI MEDIA KOMUNIKASI PADA KOMUNITAS VOICE OVER DUBBER ANNOUNCER INDONESIA - Elly Suryani; Aqil Aulia Wafda Amin; Poetut Ariyotejo Pamungkas; Bulan Khairati Wilti; Zulfikar Ali Husen; Aminah Swarnawati (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Good communication is essential to the effectiveness of any group or organization or community. One of the communities that continues to carry out activities during the pandemic through virtual meet is the Indonesian Voice Over Dubber Announcer Community (KVDAI). One of the digital platforms used in the regular weekly gathering entitled “Kopdar Virtual” is Google Meet. Furthermore, this research conducted to find out the use of google meet as an organizational communication medium at KVDAI. This research is qualitative research with descriptive data results. This research was conducted around Jakarta with two main informants, namely the Governor of KVDAI Regional 1 for the Jabodetabek and Banten regions,and Head of Public Relations and Community Cooperation, also one supporting informant the Founder of KVDAI. Based on in-depth interview results with the informants, it is clear that Google Meet as one of the conference applications is very helpful for the KVDAI Community. The community program is still working good  during the pandemic. Even though there is some minor problems,tThere are relatively no barriers while using this application as the community communication media.